Effect of music therapy on emotional resilience, well-being, and employability: a quantitative investigation of mediation and moderation - Yingjie Feng; Mingda Wang (BMC Psychology)
Abstract This study explores the impact of music therapy on emotional resilience, well-being, and employability. Through an 8-week music therapy intervention involving 256 participants, the results demonstrated that music therapy significantly enhanced participants’ emotional resilience, which in turn improved their well-being and employability. A significant positive correlation was found between emotional resilience, well-being, and employability, with well-being mediating the relationship between emotional resilience and employability. Additionally, the study identified moderating effects of age and education level, revealing that younger individuals and those with higher education levels benefit more from emotional resilience in terms of well-being and employability. These findings suggest that music therapy is an effective intervention for enhancing emotional resilience and career development, with well-being playing a crucial role in this process. Future research should continue to investigate the long-term benefits of music therapy, explore its effects across diverse populations, and incorporate objective measures and longitudinal designs to validate and expand upon these findings.